Representasi Komunikasi Asertif Ayah dan Anak dalam Film Ngeri-Ngeri Sedap (Analisis Semiotika Pierce) - Leonardo Leonardo; Suzy Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Film is part of a form of mass communication. The author conducted research on the film Missing Home on Netflix to find out the representation of assertive communication between fathers and children. This film tells the story of a husband and wife, Mr. Domu and his wife who live in a city in North Sumatra which is thick with Bataknese values and their four children who have chosen a way of life that goes against their father's wishes. The signs and gestures of the father figure named Pak Domu will be analyzed based on the semiotics of Charles Sanders Pierce. In this study the authors use conflict theory, face negotiation, assertive communication and Charles Sanders Pierce's semiotics. This research approach is qualitative with descriptive method. The data in this study were obtained through observation of the film, interviews with informants who know Bataknese culture and literature. Seven scenes were selected from the film, which consist of scenes of conflict, negotiation and assertive forms of communication that appear in each scene. The results of the study show that in the film Ngeri- Ngeri Sedap there is a family conflict beginning with Mr. Domu's attitude who forces his will on his four children so that his children and his wife protest and leave the house, then Mr. Domu negotiates by trying to adjust to his children's choices and being open on the differences and assertive communication patterns used by Mr. Domu in resolving his family conflicts. Film merupakan bagian dari bentuk komunikasi massa. Penulis melakukan penelitian pada film Ngeri-Ngeri Sedap di Netflix untuk mengetahui representasi komunikasi asertif antara ayah dan anak. Film ini menceritakan sepasang suami istri, Pak Domu dan istrinya yang tinggal di satu kota di Sumatera Utara yang kental dengan nilai dan adat istiadat Batak dan empat anaknya yang memiliki pilihan jalan hidup yang bertentangan dengan keinginan ayahnya. Tanda dan gestur tokoh ayah yang bernama pak Domu akan dianalisis berdasarkan semiotika Charles Sanders Pierce. Dalam penelitian ini penulis menggunakan teori konflik, negosiasi wajah, komunikasi asertif serta semiotika Charles Sanders Pierce. Pendekatan penelitian ini adalah kualitatif dengan metode deskriptif. Data dalam penelitian ini didapat melalui observasi pada film tersebut, wawancara dengan narasumber yang mengetahui adat istiadat Batak dan studi pustaka. Dari film Ngeri-Ngeri Sedap dipilih tujuh adegan yang terdiri dari adegan konflik, negosiasi dan bentuk komunikasi asertif yang muncul dalam setiap scenenya. Hasil penelitian menunjukan bahwa dalam film Ngeri-Ngeri Sedap terdapat konflik keluarga diawali dengan sikap pak Domu yang memaksakan kehendak kepada keempat anaknya sehingga anak anaknya juga istrinya protes dan meninggalkan rumah, lalu pak Domu melakukan negosiasi dengan mencoba menyesuaikan diri dengan pilihan anak anaknya serta bersikap terbuka pada perbedaan dan pola komunikasi asertif yang dilakukan pak Domu dalam menyelesaikan konflik keluarganya.